Hyperbaric Oxygen Therapy in Patients with COVID-19 - S. S. Petrikov; A. K. Evseev; O. A. Levina; A. K. Shabanov; V. V. Kulabukhov; N. Yu. Kutrovskaya; N. V. Borovkova; Е. V. Klychnikova; I. V. Goroncharovskaya; E. V. Tazina; K. А. Popugaev; D. A. Kosolapov; et al. (Общая реаниматология, 2020)
The aim of the study is to evaluate the efficacy of hyperbaric oxygen therapy and its effect on oxidative stress and apoptosis in patients with new coronavirus infection COVID-19.Materials and methods. 90 patients diagnosed with new coronavirus infection caused by SARS-CoV-2 virus were examined. Hyperbaric oxygen therapy sessions were conducted in 57 patients (38 in severe condition (CT 3-4), 19 in moderate condition (CT 1-2)). The procedures were performed in 1.4-1.6 ATA mode for 40 minutes, 247 sessions in total were performed. The effect of hyperbaric oxygenation was assessed by measuring the level of oxygen saturation, the severity of oxidative stress and apoptosis of blood lymphocytes.Results. In all examined patients with new coronavirus infection caused by SARS-CoV-2, positive changes such as dyspnea reduction and improvement of general well-being were registered after hyperbaric oxygen therapy sessions. The level of oxygen saturation after the end of the hyperbaric oxygen therapy course was 95.0±1.6% (before the course — 91.3±5.9%), which allowed to return almost all patients to spontaneous respiration without the need for further oxygenation therapy. Hyperbaric oxygen therapy did not reduce the total antioxidant activity, however, it was associated with a decrease in the blood malone dialdehyde from 4.34±0.52 pmol/l to 3.98±0.48 pmol/l and a decrease in open circuit potential of platinum electrode from -22.78±24.58 mV to -37.69±17.4 mV. Besides, the positive effect of hyperbaric oxygen therapy was manifested in normalization of blood cell apoptosis.Conclusion. Hyperbaric oxygen therapy in patients with new coronavirus infection caused by the SARS-CoV-2 virus is an effective treatment method with multiple effects resulting in improvement of subjective indicators of the patients' condition, increase of hemoglobin oxygen saturation, decrease of lipid peroxidation intensity, activation of antioxidant system, restoration of pro- and antioxidant balance and apoptosis normalization.